2012
DOI: 10.2147/ijn.s34349
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal injection of magnetic Fe3O4-nanoparticle induces hepatic and renal tissue injury via oxidative stress in mice

Abstract: Because of its unique magnetic properties, the iron oxide (Fe 3 O 4 ) nanoparticle has been widely exploited and its application in various fields has promised immense benefits. However, doubts exist over the use of Fe 3 O 4 -nanoparticles in human beings. Thus, the aim of the current study was to find out the potential safety range of medical use. Twenty-five Kunming mice were exposed to Fe 3 O 4 -nanoparticles via intraperitoneal injection daily for 1 week at doses of 0, 5, 10, 20, and 40 mg/kg. Hepatic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 42 publications
(47 reference statements)
1
15
0
1
Order By: Relevance
“…When under an AMF, MIONs generated enough heat to induce cell death within tumors. A separate mouse study determined that up to 5 mg/kg of MIONs can be safely delivered intraperitoneally although at higher levels, signs of oxidative damage were detected within the hepatic and renal tissues (Ma et al, 2012 ). Furthermore, monocyte/macrophage-like cells with a propensity to migrate into tumors, can be loaded with MIONs externally and injected intraperitoneally, after which the cells will direct MIONs for magnetic hyperthermia (Basel et al, 2012 ).…”
Section: Mode Of Deliverymentioning
confidence: 99%
“…When under an AMF, MIONs generated enough heat to induce cell death within tumors. A separate mouse study determined that up to 5 mg/kg of MIONs can be safely delivered intraperitoneally although at higher levels, signs of oxidative damage were detected within the hepatic and renal tissues (Ma et al, 2012 ). Furthermore, monocyte/macrophage-like cells with a propensity to migrate into tumors, can be loaded with MIONs externally and injected intraperitoneally, after which the cells will direct MIONs for magnetic hyperthermia (Basel et al, 2012 ).…”
Section: Mode Of Deliverymentioning
confidence: 99%
“…Over the last two decades there has been an increase in the use of magnetic particles and magnetic microspheres including iron oxide nanoparticles (IONPs) and superparamagnetic iron oxide nanoparticles (SPIONs) for bio-medical applications such as imaging, diagnostics, therapies and theranostics, but their suitability for these applications ultimately depends on their biodistribution and toxicity profiles [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. The two main administration routes for IONPs into the body are intravenous (IV) injection and intraperitoneal (IP) injection.…”
Section: Introductionmentioning
confidence: 99%
“…The two main administration routes for IONPs into the body are intravenous (IV) injection and intraperitoneal (IP) injection. While IP injection offers a longer plasma half-life of particles since it takes longer for the particles to reach circulation, a limited number of studies have been reported, and IV injection remains the most common clinical administration route [8,19,21,22,23,24,25,26]. Biodistribution studies have found that IONPs are localized primarily to the liver and spleen for clearance via mononuclear phagocytes [3,4,7,10,11,13,27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В ис-следовании эффекта частичного окисления («старе-ние») и модификации поверхности наночастиц Fe 0 потенциальную нейротоксичность в условиях in vitro на культурах клеток микроглии (BV2) и нейронов (N27) грызунов установлено, что частичное или по-лное окисление наночастиц Fe 0 приводит к пониже-нию их окислительно-восстановительной активнос-ти, вероятно снижает токсичность относительно клеточных культур млекопитающих [4]. Установле-но, что наночастицы Fe 3 O 4 размером 35 нм при семи-кратном внутрибрюшинном введении в дозе 40 мг/кг мышам вызывают нарушения антиоксидантно-про-оксидантного равновесия в тканях печени и почек, в пользу чего свидетельствует увеличение уровня мар-керов оксидативного стресса [13]. Таким образом, данные об образовании свободных радикалов путем окисления металлического железа (Fe 0 ) ставят во-прос о возможности участия в механизмах действия НЧЖ такого радикала, как оксида азота.…”
Section: Discussionunclassified